Spatial econometric methods in agricultural economics using R / Paolo Postiglione, Roberto Benedetti [and] Federica Piersimoni, editors. - Postiglione, Paolo; Benedetti, Roberto; Piersimoni, Federica (Boca Raton, FL CRC Press, 2022)
The methods and techniques presented in this book are focused on spatial data and its use in monitoring agricultural resources, farms management, and regional markets. The authors introduce spatial econometrics models for the different data types relevant to the statistical units adopted in typical agricultural economics analyses. The theory of each model or procedure described is complemented by examples on real data that are developed by using the open-source software R. In this way, the readers can repeat these analyses on their own data. The different phases of agricultural data collection, analysis, and integration are described in a simple and intuitive way. The joint use of statistical methods, new technologies, and economic theory is treated with particular reference to the peculiarities of spatial data for a proper and efficient analysis of agricultural data sets"--
Basic Concepts / Postiglione Paolo, Benedetti Roberto and Piersimoni Federica -- Spatial Sampling Designs / Pantalone Francesco and Benedetti Roberto -- Including Spatial Information in Estimation from Complex Survey Data / Pantalone Francesco and Ranalli Maria Giovanna -- Yield Prediction in Agriculture: A Comparison Between Regression Kriging and Random Forest / Nissi Eugenia and Sarra Annalina -- Land Cover/Use Analysis and Modelling / Carfagna Elisabetta and Di Fonzo Gianrico -- Farm Surveys (Piersimoni Salvioni Andreano) (Occorre renderlo -- molto spatial) -- Exploring Spatial Point Pattern in Agriculture / Andreano M Simona and Mazzitelli Andrea -- Spatial Analysis of Farm Data / Cartone Alfredo and Panzera Domenica -- Spatial Econometric Modelling of Farm Data / Billè Anna Gloria, Salvioni Cristina and Vidoli Francesco -- Areal Interpolation Methods: The Bayesian Interpolation Method / Panzera Domenica -- Small Area Estimation of Agricultural Data / Bertarelli Gaia, Schirripa Spagnolo Francesco, Salvati Nicola and Pratesi Monica -- Cross-sectional Spatial Regression Models for Measuring Agricultural [beta]-convergence / Cartone Alfredo and Postiglione Paolo -- Spatial Panel Regression Models in Agriculture / Postiglione Paolo.
Includes bibliographical references and index.
Keywords: Econometrics; R (Computer program language).; Geography -- Statistical methods; Spatial analysis (Statistics) -- Data processing; Agriculture -- Economic aspects -- Mathematical models